2014
DOI: 10.1002/srin.201400186
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Slag Chemistry by FTIR‐RAS and Raman Spectroscopy: Effect of Water Vapor Content in H2H2OCOCO2 Mixtures Relevant to a Novel Green Ironmaking Technology

Abstract: In an effort to develop a novel green ironmaking process with the potential of steelmaking in a single continuous process the chemistry of selected slag systems were investigated. The novel process uses gaseous fuels and reductants that help reduce energy consumption and minimize greenhouse gas emissions. Amongst the proposed reductants and fuels are H2, natural gas (NG), and coal gas (CG). In different ironmaking processes, the molten bath (iron–slag bath) is expected to be at equilibrium with gas atmospheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…6 Models of silicate melt structural entities with their Q-notation, NBO/Si ratios, and structural units in addition to showing the bridging oxygen (BO) and nonbridging oxygen (NBO), respectively [6,57] were applied to slags of interest for the Flash Ironmaking Technology (FIT), especially in terms of the effects of water vapor expected to be present in high contents in the new process [6,[55][56][57][58]. Table 1 [6,54]. In addition, the XPS and the NBO/T suggest that the studied slag is more depolymerized under a CO/CO 2 atmosphere and more polymerized under the H 2 /H 2 O atmosphere [57].…”
Section: Slag Chemistrymentioning
confidence: 99%
“…6 Models of silicate melt structural entities with their Q-notation, NBO/Si ratios, and structural units in addition to showing the bridging oxygen (BO) and nonbridging oxygen (NBO), respectively [6,57] were applied to slags of interest for the Flash Ironmaking Technology (FIT), especially in terms of the effects of water vapor expected to be present in high contents in the new process [6,[55][56][57][58]. Table 1 [6,54]. In addition, the XPS and the NBO/T suggest that the studied slag is more depolymerized under a CO/CO 2 atmosphere and more polymerized under the H 2 /H 2 O atmosphere [57].…”
Section: Slag Chemistrymentioning
confidence: 99%
“…The effect of water on the slag chemistry was further investigated in this laboratory to understand the interactions at the molecular level. [4,5,16,17] The authors also found that water affected Flow rates are calculated at 25 8C and 0.85 atm (atmospheric pressure at Salt Lake City). www.steel-research.de the distribution of P and Mn between slag and molten iron.…”
Section: Resultsmentioning
confidence: 92%
“…In this process, the more polymerized the melting slag is, the more Q n with high n is produced. As seen in Table , with slag PRD increasing, the area ratios of Q 0 and Q 1 decrease whereas the area ratios of Q 2 and Q 3 increase, leading to the increasing ψ ( ψ = ( Q 3 + Q 2 )/( Q 1 + Q 0 ), (a measure of polymerization degree) in the experimental scope. It also suggests FeO behaves as basic oxide because of the enhanced depolymerization effect on the silicon network structure with FeO increasing.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the spectrum must be deconvoluted. As Gaussian de‐convolution is widely used in silicate slag and provides good fitting results in the pre‐analysis of this work, Gaussian method is used to fit the curve and assign the individual vibrations of structural units qualitatively and quantificationally. The fitting process is firstly assumed Raman envelope according with the Gaussian distribution, and then new bands are added based on the distinguishable shoulders and peaks, as displayed in Figure b–f.…”
Section: Resultsmentioning
confidence: 99%